Pelatihan Kewirausahaan Digital Untuk Atlet Kota Semarang - Natalia Sari Pujiastuti; Julianto, Edi Nurwahyu; Saptiono, Ami (Universitas 17 Agustus 1945 Semarang, 2024)
This service activity aims to increase the potential of athletes in the world of digital entrepreneurship for athletes assisted by KONI Semarang City through entrepreneurship training in the digital field. The potential for digital businesses in Indonesia is very large and is expected to continue to grow. Therefore the main focus of this activity is to provide a better understanding of the potential outside the world of sport as well as the digital entrepreneurial skills needed to start and manage your own business. The service method is in the form of understanding the Entrepreneurial Mindset, Facilitating Business Logo Creation and Digital Entrepreneurship Skills. By involving expertise in entrepreneurship and training, this program is designed to empower athletes to create independent economic opportunities. Through this approach, it is hoped that athletes can overcome economic challenges after retiring from their sports careers and create a brighter future as successful digital entrepreneurs.